A Praxeological Analysis of Textbook: Systems of Linear Inequalities in Two Variables - Noviana Antaria Antaria; Sufyani Prabawanto (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to analyse the presentation of systems of linear inequalities in two variables in Grade X senior high school/vocational high school mathematics textbooks under the Merdeka Curriculum using a praxeological framework. This research employed a qualitative method through document analysis of the student textbook and teacher guidebook published in the 2023 revised edition. The data were analysed based on the four components of praxeology: task, technique, technology, and theory. The findings show that the textbook presents contextual and exploratory tasks that encourage students to construct mathematical models from real-life situations. However, the continuity between exploratory tasks and procedural exercises is not consistently developed. In terms of technique, students are mostly directed to use graphical methods, while alternative strategies such as numerical testing or algebraic approaches are not sufficiently explored. The technology component, which refers to the justification of techniques, is not explicitly emphasised. Similarly, the theory component is not clearly presented in the student textbook, leaving formal mathematical concepts implicit. These findings indicate that the textbook has not fully supported students’ conceptual understanding of systems of linear inequalities in two variables. Therefore, teachers play an important role in complementing, contextualising, and deepening the material presented in the textbook.